TEACHING MONOLOGICAL AND DIALOGICAL FORMS OF SPEECH IN FOREIGN LANGUAGE AT HIGH SCHOOLS - RanoAzimbayeva, NasibaMurodova (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Recently, teaching English has become very widespread. This is a social order, as modern society is unthinkable without extensive international contacts. The importance of a foreign language has become a sign of education. Learning a foreign language provides intellectual, verbal and emotional development, has a beneficial effect on the formation of the speech motor, develops phonemic hearing, a sense of language. A foreign language broadens the children’s perception of the environment, the ability to observe, compare, and establish connections. Also, the study of a foreign language forms theoretical thinking, trains all kinds of memory, develops imagination, creative abilities, and satisfies the cognitive needs of a person. In addition, a foreign language contributes to the development of social skills. Mastering a foreign language is a systematic work. Teacher teaches students to regularly and conscientiously complete their homework, actively work in the classroom, which is also important for educating the individual. And in schools and classes with in-depth study of a foreign language, the foundations of vocational training in a foreign language are laid. Recently, in the theory and methodology of teaching a foreign language, more and more attention has been paid to the problem of learning to speak English. Proficiency in a foreign language makes it possible to correctly express thoughts in this language, it is a means of live contact, which ensures the achievement of mutual understanding between people. The desire to speak a foreign language arises when people have a need to say something to each other. The motive may be the incentive of the interlocutor to take any action (communicate, prove) and non-verbal action (fulfill the request, do something).